Constructos mentales relacionados con la continuidad del uso de los aparatos ortodónticos en pacientes que han abandonado su tratamiento - Bautista Mora, Mayra Alejandra; Cárdenas Castillo, Edwin Daniel (Universidad Antonio Nariño, 2023)
Orthodontic treatment abandonment and keeping brackets in the mouth unchecked are increasingly common concerns in the orthodontic field. However, little is known about the mental constructs involved in this phenomenon. Objective: To identify the mental constructs related to the continued use of orthodontic appliances in patients who have abandoned their.